2002
DOI: 10.1074/jbc.m206925200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Inositol 1,4,5-Trisphosphate (IP3) Receptors with Synthetic Poly(ethylene glycol)-linked Dimers of IP3 Suggest Close Spacing of the IP3-binding Sites

Abstract: The distances between the inositol 1,4,5-trisphosphate (IP 3 )-binding sites of tetrameric IP 3 receptors were probed using dimers of IP 3 linked by poly(ethylene glycol) (PEG) molecules of differing lengths (1-8 nm). Each of the dimers potently stimulated 45 Ca 2؉ release from permeabilized cells expressing predominantly type 1 (SH-SY5Y cells) or type 2 (hepatocytes) IP 3 receptors. The shortest dimers, with PEG linkers of an effective length of 1.5 nm or less, were the most potent, being 3-4-fold more poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
52
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 37 publications
(67 reference statements)
5
52
1
Order By: Relevance
“…However, our localization is different from that of another electron microscopy study, which suggested the InsP 3 -binding domain is close to the 4-fold axis (8). Their conclusion was inferred from an earlier ligand binding study using dimers of InsP 3 linked by polyethylene glycol molecules of varying lengths (10 -80 Å) (28) that suggested that the InsP 3 -binding sites are separated by no more than 20 Å. This estimate is inconsistent with our map where the InsP 3 -binding sites assigned to the B domains are spaced at least 100 Å apart.…”
Section: Three-dimensional Structure Of Type 1 Insp 3 R 21321contrasting
confidence: 99%
See 1 more Smart Citation
“…However, our localization is different from that of another electron microscopy study, which suggested the InsP 3 -binding domain is close to the 4-fold axis (8). Their conclusion was inferred from an earlier ligand binding study using dimers of InsP 3 linked by polyethylene glycol molecules of varying lengths (10 -80 Å) (28) that suggested that the InsP 3 -binding sites are separated by no more than 20 Å. This estimate is inconsistent with our map where the InsP 3 -binding sites assigned to the B domains are spaced at least 100 Å apart.…”
Section: Three-dimensional Structure Of Type 1 Insp 3 R 21321contrasting
confidence: 99%
“…This estimate is inconsistent with our map where the InsP 3 -binding sites assigned to the B domains are spaced at least 100 Å apart. A possible explanation for this discrepancy is that the radioligand binding studies were performed at pH 8.3 (28), which is optimal for binding of InsP 3 , while our study and the heparin-binding site mapping study (26) used a pH of 7.4. Conformational transitions may take place in the channel upon changing the pH as suggested previously (27).…”
Section: Three-dimensional Structure Of Type 1 Insp 3 R 21321mentioning
confidence: 86%
“…Our 3D structure (determined in the absence of Ca 2ϩ ), which measures about 18 ϫ 18 ϫ 18 nm and is approximately square in both top and side projections, corresponds more closely with the square structure observed by Hamada et al (31). However, the peripheral location of the IP 3 -binding domain suggested by heparin-gold labeling (31) is not consistent with recent studies (32) suggesting that the IP 3 -binding sites within a tetrameric receptor are no more than 2 nm apart. It is possible that the large size of the heparin, gold, and linker may have exaggerated the separation of the IP 3 -binding sites in the labeling study (31).…”
Section: Comparison With Previous Structural Data On the Ip3rsupporting
confidence: 75%
“…Results from both limited proteolysis and measurements of the location and properties of the IP 3 -binding sites can be used as guides to assign these domains. The tetrameric IP 3 R has a single IP 3 -binding site on each subunit, located between residues 226 and 576 (9), and recent studies with dimeric molecules of IP 3 suggest that the sites are likely to be separated by no more than Ϸ2 nm (32). On this basis, the petal subdomains in our 3D map are unlikely to contain the IP 3 -binding sites, because equivalent sites within these subdomains are at least 8 nm apart (Fig.…”
Section: Comparison With Previous Structural Data On the Ip3rmentioning
confidence: 72%
“…The His 6 -tagged fusion proteins were expressed in Escherichia coli (19) and cleaved from their His 6 tags using thrombin. Equilibrium-competition binding assays using 3 H-IP 3 (0.7 nM) were performed and analyzed as reported previously (19).IP 3 -evoked Ca 2ϩ Release-The ER of DT40 cells was loaded with a low affinity Ca 2ϩ indicator (Mag fluo-4), and IP 3 -evoked Ca 2ϩ release was measured from the saponin-permeabilized cells using a FlexStation as previously reported (20).Single Channel Recording-Single channel currents were recorded in the whole-cell configuration or from excised patches of nuclear envelope using the patch clamp technique exactly as reported (10). Except where indicated otherwise, bath solution (BS) contained 140 mM KCl, 10 mM Hepes, 500 M BAPTA (1,2-bis(2-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid), 270 M CaCl 2 (free [Ca 2ϩ ] ϭ 246 nM), pH 7.1, and pipette solution contained: 140 mM KCl, 10 mM Hepes, 100 M BAPTA, 48.7 M CaCl 2 (free [Ca 2ϩ ] ϭ 212 nM), 500 M ATP, pH 7.1, and IP 3 (usually 10 M).…”
mentioning
confidence: 99%